Work and solidarity economy in the identity formation of the Florestan Fernandes Settlement/Trabalho e economia solidária na formação identitária do Assentamento Florestan Fernandes - Danilo Assunção da Silva; Ricardo Oliveira da Silva (Universidade Estadual de Alagoas, 2020)
This paper aimed to present the importance of Work and the solidarity economy in the process of forming the identity of the Florestan Fernandes Settlement, located in the Canindé de São Francisco, in the State of Sergipe. Oral history was used as a research method to understand the work carried out with the young people of the settlement, aiming to develop initiatives of creative and solidary economy, and the importance of this work for the strengthening of the collective identity of the settlement and for the construction of the protagonism of the settlers. young people based in the community and conducting their own history. The article aims to contribute to demonstrate the importance of oral history as a method of research in history and to reaffirm the social importance of settlements as alternative spaces of organization and resistance.